The influence of working capital and company size on financial performance in SOE Banking Company - Astutik, Endang Puji; Rohman, Abdul (Privietlab, 2023)
This research aims to determine the effect of working capital and company size on the financial performance of state-owned banking companies listed on the IDX. The population of this research is state-owned banking companies registered on the IDX from 2010 - 2019. In this research, 40 samples from 4 companies were taken using the purposive sampling method and observed for ten years. This research uses the e-views ten application. The study results show that working capital with a specification of 0.5830 > 0.05 does not affect financial performance. Company size with a specification of 0.0243 <0.05 affects financial performance. Working capital and company size with a specification value of 0.000000 <0.05 simultaneously affect financial performance